CASE REPORT: SUBCLAVIAN VEIN THROMBOSIS TREATED BY PULSE-SPRAY THROMBOLYSIS USING A RETROGRADE APPROACH - Wong, DES; Leong, KH; Feng, PH; Chee, TSG (The ASEAN Journal of Radiology, 2023)
We report a case of subclavian vein thrombosis in a 44 year old lady with SLE that was successfully treated with transcatheter thrombolytic techniques. The treatment was unusual in that a retrograde approach to the thrombosed vessel had to be employed due to the failure to canulate a distal peripheral vein. We also used the Pulse Spray technique to administer the thrombolytic drugs, the technique being originally described for thrombolysis in the arterial system. The patient has been followed up for 8 months with no recurrence of the problem.